Nerve Fiber Layer Thickness and Characteristics Associated with Glaucoma in Community Living Older Adults: Prelude to a Screening Trial?. (4th March 2017) - Klein, Barbara E. K.; Johnson, Chris A.; Meuer, Stacy M.; Lee, Kyungmoo; Wahle, Andreas; Lee, Kristine E.; Kulkarni, Amruta; Sonka, Milan; Abràmoff, Michael D.; Klein, Ronald
ABSTRACT: Purpose : To examine the associations of nerve fiber layer (NFL) thickness with other ocular characteristics in older adults. Methods : Participants in the Beaver Dam Eye Study (2008–2010) underwent spectral domain optical coherence tomography (SD-OCT) scans of the optic nerve head, imaging of optic discs, frequency doubling technology (FDT) perimetry, measurement of intraocular pressure (IOP), and an interview concerning their history of glaucoma and use of drops to lower eye pressure. Self-reported histories of glaucoma and the use of drops to lower eye pressure were obtained at follow-up examinations (2014–2016). Results : NFL thickness measured on OCTs varied by location around the optic nerve. Age was associated with mean NFL thickness. Mean NFL was thinnest in eyes with larger cup/disc (C/D) ratios. Horizontal hemifield defects or other optic nerve-field defects were associated with thinner NFL. NFL in persons who reported taking eye drops for high intraocular pressure was thinner compared to those not taking drops. After accounting for the presence of high intraocular pressure, large C/D ratios or hemifield defects, eyes with thinner NFL in the arcades were more likely (OR = 2.3 for 30 micron thinner NFL, p = 0.04) to have incident glaucoma at examination 5 years later. Conclusion : Retinal NFL thickness was associated with a new history of self-reported glaucoma 5 years later. A trial testing the usefulness of NFL as part of a screening battery for predicting glaucoma in those previously undiagnosed might lead to improved case finding and, ultimately, to diminishing the risk of visual field loss.